Potassium Channel Blockade Enhances Atrial Fibrillation–Selective Antiarrhythmic Effects of Optimized State-Dependent Sodium Channel Blockade. Issue 23 (8th December 2015) - Aguilar, Martin; Xiong, Feng; Qi, Xiao Yan; Comtois, Philippe; Nattel, Stanley
Abstract : Background—: The development of effective and safe antiarrhythmic drugs for atrial fibrillation (AF) rhythm control is an unmet clinical need. Multichannel blockers are believed to have advantages over single-channel blockers for AF, but their development has been completely empirical to date. We tested the hypothesis that adding K + -channel blockade improves the atrium-selective electrophysiological profile and anti-AF effects of optimized Na + -channel blockers. Methods and Results—: Realistic cardiomyocyte-, tissue-, and state-dependent Na + -channel block mathematical models, optical mapping, and action potential recording were used to study the effect of Na + -current ( I Na ) blockade with or without concomitant inhibition of the rapid or ultrarapid delayed-rectifier K + currents ( I Kr and I Kur, respectively). In the mathematical model, maximal AF selectivity was obtained with an inactivated-state Na + -channel blocker. Combining optimized Na + -channel blocker with I Kr block increased rate-dependent and atrium-selective peak I Na reduction, increased AF selectivity, and more effectively terminated AF compared with optimized Na + -channel blocker alone. Combining optimized Na + -channel blocker with I Kur block had similar effects but without I Kr block–induced ventricular action potential prolongation. Consistent with the mathematical model, in coronary-perfused canine hearts, the addition of dofetilide (selective I Kr blocker) to pilsicainide (selective I Na blocker) produced enhanced atrium-selective effects on maximal phase 0 upstroke and conduction velocity. Furthermore, pilsicainide plus dofetilide had higher AF termination efficacy than pilsicainide alone. Pilsicainide alone had no statistically significant effect on AF inducibility, whereas pilsicainide plus dofetilide rendered AF noninducible. Conclusions—: K + -channel block potentiates the AF-selective anti-AF effects obtainable with optimized Na + -channel blockade. Combining optimized Na + -channel block with blockade of atrial K + currents is a potentially valuable AF-selective antiarrhythmic drug strategy. Abstract : Supplemental Digital Content is available in the text.